Progression of Anterograde Trans-Synaptic Degeneration in the Human Retina Is Modulated by Axonal Convergence and Divergence. (2nd November 2019) - Panneman, E.L.; Coric, D.; Tran, L.M.D.; de Vries-Knoppert, W.A.E.J.; Petzold, A.
ABSTRACT: In the visual pathway of patients with multiple sclerosis (MS), the inner nuclear layer (INL) of the retina is a tight barrier for retrograde trans-synaptic degeneration. In this observational, retrospective cross-sectional study, segmented macular spectral domain optical coherence tomography (OCT) volume scans were reviewed to investigate if this observation also holds true for anterograde trans-synaptic degeneration. Significant thinning was found in all retinal layers in patients with outer retinal diseases compared with the healthy controls, while there was no significant attenuation of the outer retina in patients with MS. In contrast to the tight barrier function observed with retrograde trans-synaptic degeneration, the INL appears to be more permissive for the propagation of anterograde trans-synaptic degeneration. We speculate that this may be due to the size of the area affected and be explained by convergence and divergence of axons within the retinal layers. These findings are likely relevant to future restorative stem cell treatment of the outer retinal layers, as time may matter.